56 Novel heart failure biomarker CLEC3B is associated with cardiac fibrosis, and impacts cardiac fibroblast cell function. (6th October 2022) - Edgar, K; Glezeva, N; Tonry, C; Rammos, A; Gallagher, J; Ledwidge, M; Naka, K; McDonald, K; Grieve, D; Watson, C
Abstract : Background: Using a proteomics approach we have recently identified a novel blood-based biomarker for heart failure called CLEC3B, which exhibits improved diagnostic accuracy over BNP. We have previously investigated CLEC3B expression in human atrial and ventricular tissue and shown that it correlates positively with the degree of cardiac tissue fibrosis. The purpose of this study was to validate the diagnostic potential of CLEC3B within a symptomatic population containing both cases and controls, and to determine its role in development of cardiac fibrosis and dysfunction associated with heart failure (HF). Methods: Through a HORIZON 2020 collaboration, 54 symptomatic patients were recruited from St Michael's Hospital, Dublin and University Hospital of Ioannina (Greece), over a 6-month period. The recruited cohort consisted of 20 hypertensive or obese non-HF patients with symptoms of breathlessness, and 34 patients diagnosed with acute HF. Plasma samples were collected and CLEC3B was quantified using ELISA. As the primary cell type contributing to cardiac fibrosis is the fibroblast, parallel in vitro studies were carried out using primary human cardiac fibroblast cells (HCF). Both CLEC3B gene over-expression and gene knock-down studies were carried out in HCFs, in the presence or absence of stimulation with the pro-fibrotic growth factor TGFβ. The impact of modulating endogenous CLEC3B levels on gene and protein expression was studied, including by RNA sequencing, to identify the potential role of CLEC3B in fibroblast cells. An in vivo model of angiotensin II induced HF in CLEC3B knock out mice was also conducted to study the impact of CLEC3B on cardiac function and remodelling (echocardiography, histology, gene and protein analysis). Results: Within a breathless cohort, circulating CLEC3B levels were significantly reduced by approximately 30% in acute HF patients compared to non-HF patients (P<0.0001). Receiver operating characteristic (ROC) predictive modelling of plasma CLEC3B in non-HF vs. acute HF patients showed area under the curve, AUC=0.92. RNA sequencing analysis of HCF cells showed significant changes in over 2000 genes following both CLEC3B over-expression and knockdown, with different genes being modulated depending on activation status of the HCF cells. Our mouse model of angiotensin II induced HF showed that there was an impact of global CLEC3B knockout on the expression of genes related to fibrotic processes. Conclusions/Implications: These data show that CLEC3B shows promise as a diagnostic tool that could help identify HF patients within a symptomatic breathless population. It also highlights that CLEC3B may have an important role in the development and progression of fibrosis associated with cardiac remodelling in heart failure, due to the impact on function of activated cardiac fibroblasts in both in vitro and in vivo experimental models. This aspect opens up the possibility of CLEC3B being a potential novel therapeutic target in diseases associated with cardiac fibrosis and remodelling.